Application of diffuse discharges of atmospheric pressure formed by runaway electrons for modification of copper and stainless steel surface; Physics of Atomic Nuclei; Vol. 78, iss. 14 - Tarasenko V. F. Victor Fedotovich (2015, 2015)
Title screen